Egalitarian equivalence under asymmetric information - Geoffroy de Clippel; David Pérez-Castrillo; David Wettstein (Brown University, Department of Economics, 2010)
We propose a definition of egalitarian equivalence that extends Pazner and Schmeidler's (1978) concept to environments with incomplete information. If every feasible allocation rule can be implemented by an incentive compatible mechanism (as, for instance, in the case of non-exclusive information), then interim egalitarian equivalence and interim incentive efficiency remain compatible, as they were under complete information. When incentive constraints are more restrictive, on the other hand, the two criteria may become incompatible.
Keywords: D62; C71; 330; Pareto Efficiency; Egalitarian Equivalence; Asymmetric Information